Risk factors and prediction model for low-birth-weight infants born to women with gestational diabetes mellitus - Pan, Yu-qing; Huang, Xin-xin; Jiang, Xiu-min (Frontiers in Public Health, 2024)
To explore the risk factors for low-birth-weight infants born to pregnant women with GDM to develop a prediction model and to construct a prediction nomogram for the risk of low birth weight infants born to pregnant women with GDM.The clinical data of singleton infants diagnosed with gestational diabetes mellitus in Southeast China in 2019 were retrospectively reviewed. Gestational conditions and neonatal weight were assessed.A total of 386 diabetic mothers and infants were enrolled, including 193 in the low birth weight group and 193 in the normal birth weight group. The statistically significant factors were age over 36 years (OR=1.916, 95% CI 1.048-3.505), junior high school education (OR=4.454, 95% CI 1.882-10.543), history of fetal distress (OR=0.120, 95% CI 0.016-0.925), gestational hypertension (OR=3.681, 95% CI 1.357-9.986), preeclampsia (OR=24.652, 95% CI 5.956-102.036), threatened preterm birth (OR=18.393, 95% CI 8.457-39.999), triglycerides (OR=0.642, 95% CI 0.485-0.850), and inadequate gestational weight gain (OR=1.997, 95% CI 1.162-3.432). The area under the receiver operating characteristic curve (AUC) was 0.834 (95% CI: 0.794-0.874, P<0.001), and the sensitivity and specificity were